Application of Conjugable Oxidation Products Assay in Assessment of Gamma-Irradiated Palm Olein - Endinkeau, Kuang; Woodward, T. W. (1990)
Samples ojpalm olein were irradiated with y-rays up to 12kGy. The extent ojperoxidation in irradiated samples was determined by conjugable oxidation products (COP) assay and the result were compared with the UV absorbance at 232 nm. The two parameters were poorly correlated (r = 0.6321) within the range ofdoses used. The ifJect ofy-irradiation is mainly to oxidise linoleic acid (C18:2) as this component is the major diunsaturatedJatty acid in palm oil.